Evaluación de la concentración de omega 3 del huevo de codorniz (Coturnix coturnix), con dietas que incluye linaza (Linum usitatissimum) y chia (Salvia hispánica) - Almeida Almeida, Abel Andrés (2024)
The present research is oriented to the nutritional characteristics of flaxseed (Linum usitatissimum) and chia (Salvia hispanica) as sources of fatty acids, by feeding these ingredients will help to increase the concentration of Omega 3 in quail eggs. The general objective is to evaluate the Omega 3 concentration of quail eggs with diets that include flaxseed and chia. The methodology was of an explanatory type, and it was implemented in an Experimental Design of Completely Randomized Blocks (DBCA) with five treatments and two replications, in addition to this, an analysis of variance and a 5% Tukey test were used, where a total of 100 quails of 5 weeks of age were used, being the treatments the following: T0 Control (commercial feed), T1 (commercial feed + 20% flaxseed), T2 (commercial feed + 10 flaxseed), T3 (commercial feed + 20% chia) and T4 (commercial feed + 10% chia); these treatments did not show significant differences (p < 0,05) for the variables: number of eggs per week, egg weight (gr), shape index (%), laying percentage (%), eggshell thickness (mm), egg mass (gr) and yolk coloration. The results of the bromatological and chromatographic analyses allowed determining statistically the best treatment, concluding that the addition of 20% chia in the feed was determined as the optimal dose to obtain the highest percentages in the nutritional composition of the egg, registering 13,9% protein, 73,2% moisture, 11,2% fat, 0,4% carbohydrates, 1,3% ash and 9,30% Omega 3.